Penanganan delayed eruption karena impaksi gigi insisivus sentralis kiri dengan surgical exposure pada anak - Harun Achmad (DiscoverSys Inc., 2009)
Delayed eruption is one of dental eruption deviation characterized by delay of dentaleruption. Delayed eruption can be caused by local factor such as impacted tooth. Thiscan be managed surgically and then orthodontically brought into the dental arch. Aneleven years old girl came to the dental clinic specialist of FKG-UNPAD Bandung,with the chief complaint of having non-erupted upper left permanent central incisor,without retention of 61. Other 3 upper incisor, 11, 22, 12 have erupted normally.Panoramic examination showed impacted 11 in the alveolar bone with complete apexformation. Following the cephalometric and model analysis, the fixed orthodonticappliances were placed, followed by surgical exposure to open the impacted area thenplaced an orthodontic bracket with an attached chain to apply orthodontic forces onthe tooth to aid its movement into the line of occlusion. After 6 months treatment,patient’s esthetics and masticatory function were obtain, marked by normal position of21 in the arch.